The Transformative Power of Storytelling-Based Design Thinking: Using Diverse Feedback to Impact Aggression and Empathy in Students - Abolhassani, Zahra; Dehghani, Marzieh; Mohamadhasani, Nasrin (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: In recent decades, school aggression has increased dramatically, and the use of new practical approaches, such as design thinking, has increased. Therefore, this research was conducted to achieve more objective and comparable results to previous research and to investigate the effect of educational intervention based on design thinking using storytelling on aggression and empathy with feedback adjustment. Materials and Methods: The researchers administered the Aggression and Empathy Scale to 120 students at a public school in Tehran. After evaluating the initial results, selected students (n: 80) were randomly assigned into four groups. Designing and implementing an intervention program Positive results were obtained by implementing a one-semester intervention program based on design thinking and storytelling which incorporated diverse feedback for one semester. Results: The results showed that training based on the design thinking approach using storytelling effectively reduces aggression and increases empathy. Feedback also moderates this relationship. The results of the MANOVA test for aggression F=8.214, η2 = 0.250 showed a significant difference in students' performance after the intervention program. Also, empathy data F(1, 72) = 6.712, η2 = 0.214 confirmed the difference in empathy levels after training. (p< 0.05). Conclusion: Design thinking using thinking and creativity skills as an innovative and promising educational approach can influence positive outcomes for children's social and emotional development. The study also underscores how feedback can be used to shape students' behavior and feelings, making it relevant to teachers and those involved in policy-making concerning education.